2017
DOI: 10.1111/cea.12921
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach allergen serine proteinases: Isolation, sequencing and signalling via proteinase‐activated receptor‐2

Abstract: SUMMARY BACKGROUND Allergy to the German cockroach (Blattella germanica) is a significant asthma risk factor for inner-city communities. Cockroach, like other allergens, contains trypsin-like enzyme activity that contributes to allergenicity and airway inflammation by activating proteinase-activated receptors (PARs). To date, the enzymes responsible for the proteolytic activity of German cockroach allergen have not been characterized. OBJECTIVES We aimed to identify, isolate and characterize the trypsin-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
0
27
1
Order By: Relevance
“…P Յ 0.05, *significant differences between bracketed experiments; #significant differences from saline control. mite (59,63), and cockroach (42,50,60). The protease described here differs considerably from the recently described vacuolar serine protease from Alternaria, Alt a 15 (21).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…P Յ 0.05, *significant differences between bracketed experiments; #significant differences from saline control. mite (59,63), and cockroach (42,50,60). The protease described here differs considerably from the recently described vacuolar serine protease from Alternaria, Alt a 15 (21).…”
Section: Discussioncontrasting
confidence: 53%
“…The serine protease activity-based probe (ABP) Biotin-Pro-Lys-diphenylphosphonate was synthesized and graciously provided for our studies by Dr. Brendan Gilmore, Queens University School of Pharmacy, Belfast, UK. Covalent labeling of enzymes in the Alternaria filtrates and crude cellular antigen, as well as in chromatographic column fractions isolated from these sources, was achieved essentially as described previously (28,50), with minor modifications. The Alternaria samples were diluted to a final concentration of 1.5 U/ml and incubated with 100 M of the ABP in a 10-l reaction volume consisting of: 50 mM Tris•HCl, pH 8, 0.1% NP40, and 1.5 mM CaCl2 for 2 h at room temperature to biotinylate the enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, detection of active proteases is dependent on their affinity towards the ABP that is used. We have previously used this approach successfully to identify active serine proteases upregulated in the setting of a murine model of infectious colitis 14 and to determine the sequences of serine proteases present in complex allergenic cockroach extracts 15 . Here, we performed a study to profile and identify active serine proteases secreted by the colonic mucosa of control and IBD patients by using ABPs.…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, PAR-2 plays a crucial role in different animal models of intestinal diseases, focal segmental glomerulosclerosis, skin inflammatory diseases, myocarditis, and airway inflammation. [12][13][14][15][16][17][18][19] Recent studies have shown that human corneal epithelial cells express PAR-2. In human corneal epithelial cells, inhibition of PAR-2 by a specific antagonist prevents proinflammatory cytokine production and reduces inflammation induced by Acanthamoeba plasminogen activator, a serine protease secreted by Acanthamoeba trophozoites, that is involved in the pathogenesis of Acanthamoeba keratitis, indicating that disruption of PAR-2 activity might have a major impact on preventing inflammatory responses in Acanthamoeba keratitis.…”
mentioning
confidence: 99%